The Economic and Social Determinants of Migrants' Well-Being during the Global Financial Crisis - Alexander M. Danzer; Barbara Dietz (Institute of Labor Economics (IZA), 2018)
This paper investigates the economic and social determinants affecting the well-being of temporary migrants before, during and after the financial crisis. Exploiting unique panel data which cover migration spells from Tajikistan between 2001 and 2011, we find that migrants earn less but stay longer in the destination during the crisis; at the same time, they become more exposed to illegal work relations, harassment and deportation through the Russian authorities. Especially illegal employment has negative second order effects on wages. Despite the similarities in the demographics and jobs of migrant workers, we find substantial heterogeneity in how the financial crisis affects their well-being. Migrants who experience wage losses during the crisis rationally stop migrating.
Keywords: J15; J46; I31; 330; migration; informal employment; deportation; harassment; financial crisis; well-being; Russia